Testing the Test Using Rasch Measurement Model: Can Expert Vetting Ensure Quality of Test Items? - Arunodaya, Barman; Ahmad Fuad, Abdul Rahim; Md. Anayet, Ullah (2016)
Introduction: Item analysis using Rasch measurement model provides a way of measuring the quality of questions, assess how appropriate they are for the candidates and how well they measure their ability.